Penerapan Prinsip Vicarious Liability dalam Pertanggungjawaban Perseroan Terbatas - Lana Aulia Afiftania; Dian Purnama Anugerah (Fakultas Hukum Universitas Airlangga, 2022)
AbstractA limited liability company is a legal subject capable of being responsible for the risks in carrying out its business. The principle of vicarious liability is the basis of a person’s responsibility for acts against the law of others. One of these principles is applied in the employer’s responsibility to his subordinates. This research is a legal research that uses a statutory approach, a conceptual approach, and a case approach. This study aims to analyze the legal relationship between a limited liability company and an employee related to the principle of vicarious liability and the liability of a limited liability company in the consideration of the panel of judges. The results of this study indicate that a limited liability company is able to act as an employer and hiring employees. According to the principle of vicarious liability, the company will be responsible if an employee causes a loss during the performance of their duties. The panel of judges recognizes the principle of vicarious liability as the basis for corporate liability. There is a lot of diversity in the implementation of these principles. However, the important elements of the principle of vicarious liability are still reflected in the considerations of the panel of judges.Keywords: Liability; Limited Company; Vicarious Liability Principle. AbstrakPerseroan terbatas merupakan subjek hukum yang mampu bertanggung jawab atas risiko dalam pelaksanaan usahanya. Prinsip vicarious liability merupakan dasar pertanggungjawaban seseorang atas perbuatan melawan hukum orang lain. Salah satu prinsip tersebut diterapkan dalam pertanggungjawaban majikan terhadap bawahannya. Penelitian ini merupakan penelitian hukum yang menggunakan pendekatan perundang-undangan (statute approach), pendekatan konseptual (conceptual approach), dan pendekatan kasus (case approach). Penelitian ini bertujuan untuk menganalisis hubungan hukum perseroan terbatas dan karyawan terkait prinsip vicarious liability serta pertanggungjawaban perseroan terbatas dalam pertimbangan majelis hakim. Hasil penelitian ini menyatakan bahwa perseroan terbatas mampu berkedudukan sebagai majikan dan mempekerjakan karyawan. Menurut prinsip vicarious liability, perseroan akan bertanggung jawab bilamana karyawan menimbulkan kerugian selama pelaksanaan tugasnya. Majelis hakim mengakui prinsip vicarious liability sebagai dasar pertanggungjawaban perseroan. Timbul banyak keberagaman dalam implementasi prinsip tersebut. Akan tetapi, unsur-unsur penting prinsip vicarious liability tetap tercermin dalam pertimbangan-pertimbangan majelis hakim.Kata Kunci: Pertanggungjawaban; Perseroan Terbatas; Prinsip Vicarious Liability.